GROWTH OF Spirulina platensis IN INDOOR AND SEMI OUTDOOR CULTURING SYSTEMS - Nainggolan, Judita Grace Merry; Tanjung, Afrizal; Effendi, Irwan (Asian Journal of Aquatic Sciences, 2018)
Microalgae are very potential to be developed as biofuel feedstocks when compared to food crops because they have several advantages such as rapid growth, high productivity, enabling the use of freshwater and seawater, and production costs are not too high. Spirulina platensis has a high nutrient content so it is used as a health food ingredient. Once the importance of the role of nutritional value of S. platensis for humans and some marine organisms, then the right culture medium to get the maximum nutritional content needs to be studied more deeply. This study aims to determine the effect of different doses of nutrition on the density of biomass cultivation of S. platensis microalgae with indoor and semi outdoor system. This research has been conducted from April to May 2018. The method by used the experimental method. The data obtained were analyzed statistically using simple linear regression equation. The results showed that the influence in the dose of nutris media guillard, S.platensis increased with the dose of nutrients as much as 0.60 ml either indoor or semi outdoor system. As for the amount of biomass density S. platensis in the semi-outdoor system the amount of biomass density is higher than the indoor system